2020
DOI: 10.5194/sd-27-1-2020
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity of drilling fluids from 3000 m deep Koyna pilot borehole provides insights into the deep biosphere of continental earth crust

Abstract: Abstract. Scientific deep drilling of the Koyna pilot borehole into the continental crust up to a depth of 3000 m below the surface at the Deccan Traps, India, provided a unique opportunity to explore microbial life within the deep granitic bedrock of the Archaean Eon. Microbial communities of the returned drilling fluid (fluid returned to the mud tank from the underground during the drilling operation; designated here as DF) sampled during the drilling operation of the Koyna pilot borehole at a depth range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 99 publications
(121 reference statements)
0
8
0
Order By: Relevance
“…Kowalczyk et al, 2016;Muhonja et al, 2018;Park and Kim, 2019). Regarding the microorganisms of drilling fluids used in deep subsurface drilling operations, various studies have reported their taxonomic versatility and biodegradation potential (Alekhina et al, 2007;Bilkay, 2017, 2018;Bose et al, 2020). Plastic metabolizing ability of such bacteria, however, has not been explored in detail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kowalczyk et al, 2016;Muhonja et al, 2018;Park and Kim, 2019). Regarding the microorganisms of drilling fluids used in deep subsurface drilling operations, various studies have reported their taxonomic versatility and biodegradation potential (Alekhina et al, 2007;Bilkay, 2017, 2018;Bose et al, 2020). Plastic metabolizing ability of such bacteria, however, has not been explored in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Waste plastic samples were collected from the local landfill site (designated as P) inside the IIT Kharagpur campus (22 • 18' 45.3" N 87 • 19' 28.1" E). The drilling fluid (designated as DF2, DF4, DF7) samples were collected during a 3 km deep pilot borehole (KFD-1) drilling in the Koyna region (17 • 24' 6" N 73 • 45'8" E) of the Deccan Traps, Maharashtra under the pilot phase of the Koyna scientific drilling project (Bose et al, 2020;Roy and Bansal, 2020). The various depths were as follows: DF2: 1901.255 mbs; DF4:2335.62 mbs; DF7: 2908.52 mbs (mbs: meters below surface).…”
Section: Pe Materials Samples For Microbiological Isolation Media Amentioning
confidence: 99%
“…Members of the Cyanobacteria class and the Acidithiobacillus , Acidovorax , Desulfosporosinus , Pseudomonas , Sulfobacillus and Tessaracoccus genera were detected in 13 out of 19 analysed intervals, using at least three independent methodologies. As mentioned, Cyanobacteria had been previously reported in several drilling operations (Bose et al, 2020 ; Dutta et al, 2018 ; Gihring et al, 2006 ; Momper, Reese, et al, 2017 ) and in samples from borehole BH10 (Puente‐Sánchez et al, 2018 ), indicating the existence of non‐photosynthetic alternative metabolisms, such as the use of H 2 , in this important group of microorganisms. Moreover, we have previously isolated and characterized an endogenous IPB subsurface nitrate‐reducing bacterium from the same drilling, Tessaracoccus lapidicaptus (Puente‐Sánchez, Sánchez‐Román, et al, 2014 ).…”
Section: Discussionmentioning
confidence: 77%
“…These aerobic members included Thaumarchaeota (proved to be AOA in the following phylogenetic analysis, about 12.8% in relative abundance in the biofilm sample) [ 41 , 42 ], Gaiella (6.6%) [ 43 ], Methylobacterium (6%) [ 44 ], and Solirubrobacter (1.7%) [ 45 ]. The high abundance of aerobes distinguish the microbial community in the CCSD biofilm sample from most anaerobe-dominated microbial communities of the continental subsurface [ 46 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%